ON OPTIMAL CONTROL OF DYNAMIC SYSTEMS USING THE ALGORITHM OF NUMERICAL METHODS - HRUBINA, Kamil; JADLOVSKA, Anna (Trends in education, 2008)
The paper solves the problem of the dynamic system optimal control or process. Behaviour of the dynamic system is described by the system of differential equations. In order to solve the defined task of optimal control, the author presents the created algorithm based on the successive approximations method. The algorithm was realised within MS Excel environment.
Keywords: optimal control; algorithm of the successive approximations method; Hamilton function